PENGARUH LAYANAN PENDIDIKAN PEMAKAI TERHADAP PEMANFAATAN PERPUSTAKAAN DI UPT. PERPUSTAKAAN UNIVERSITAS MAHASARASWATI DENPASAR - Devi, Ni Putu Ayu Laksmi; Suhartika, I Putu; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
User education services are a process in which library users are made aware of the vast number of library resources, services, and information resources available to users, and taught how to use these resources. User education service is an activity to guide or give instructions to users and potential users of UPT. Mahasaraswati Denpasar University Library. The purpose of this study was to determine the effect of user education services on library utilization at the Library of UPT. Mahasaraswati University Denpasar. This study discusses the effect of user education services on library utilization at the Library of UPT. Mahasaraswati Denpasar University by using quantitative research methods. The data analysis technique of this research uses validity test, reliability test, descriptive data analysis and simple linear regression analysis using SPSS (Statistical Package Social Science) software. The results of this study indicate that there is a significant influence between user education services on library utilization at the Library of Mahasaraswati University Denpasar . Keywords: College Libraries, Library Services, User Education Services, Library Utilization